EFFORTS PERFORMED BY HOTELS IN BALI IN LOOKING AFTER THE ENVIRONMENT - Dalem, A.A.G. Raka; Widana, I.N.; Simpen, I.N.; Artawan, I.N. (Bumi Lestari; Vol 10 No 1 (2010), 2010)
A study on â€œEfforts perpormed by hotels in Bali in looking after the environmentâ€ was undertaken in 2009, by utilising data from July, 2008 until June, 2009. Objectives of the study was for collecting data on any efforts undertaken by hotels in looking after the environment especially related to minimising water consumption, garbage handling, the use of chemicals (especially cleaning chemicals), minimising energy consumption and ecosystem conservation (measured from the proportion of natural vegetation). Data were collected from interviews, document checkings and distributing questionaires. Results of the study showed that in average water consumption of hotels in Bali was 115 litres / guest night. It was considered low, less than the benchmark of Green Globe/Earthcheck which was 1,300 litres / guest night. The average of energy consumption was 0.322 MJ per guest night, which was still much below the baseline levels / standard of 340 MJ / guest night. In average garbage/waste produced by hotels was 0.0309 litre/guest night. This was also much below the baseline of 6 litres / guest night. The use of biodegradable cleaning chemicals in the hotel was averaged 35% which should be a minimum of 50%. There were 22% only of hotels which used cleaning chemicals that were biodegradable over 50% (over the standard). In average the proportion of natural vegetation in a hotel was 29%. There were 43% of sampled hotels of which their natural vegetation was over the baseline of 33%. Thus, hotels in Bali should improved their performance in looking after the environment, especially dealing with cleaning chemicals and ecosystem conservation. In this regards, they should increase the proportion of the use of biodegradable cleaning chemicals and increase the proportion of land kept with their natural vegetation.